The perception of special education teacher in teaching students with dyslexia - Wai Wai Lim; Kee Jiar Yeo; Lina Handayani (Institute of Advanced Engineering and Science, 2022)
Language learning is the biggest challenge for students with dyslexia. Therefore, special education teachers play a pivotal role in assisting students with dyslexia to mitigate any difficulties in their language learning process. This study explored the perception of special education teachers in terms of their experience, challenges faced, and strategies adopted to assist students with dyslexia in the learning process. A semi-structured interview session was conducted with three participants from three primary schools under the Special Education Integration Program (SEIP) Dyslexia Program. The findings indicated that it was challenging for special education teachers to teach students with dyslexia because they lacked the effective teaching methods and resources. Based on their teaching experiences, students with dyslexia encountered difficulties in phoneme-grapheme associations, sound blending, and segmentation. Additionally, the participants perceive that the adoption of a multisensory approach and the utilisation of mobile learning applications are two effective strategies to improve the teaching of language to students with dyslexia. Lastly, this study provided vital findings to be used as research materials by other like-minded researchers in the future.